A preliminary study to compare the prediction error of postoperative refraction in paediatric cataract surgery between 2 different intraocular lens power calculation formulas - Azlyn Azwa, Jasman (2008)
The treatment of paediatric cataracts has progressed tremendously in the past 15 to 20 years. There is a growing trend towards intraocular lens implantation in infants and younger children whose eyes are still undergoing rapid growth and refractive changes. Objective This study is intended to assess the predictability of desired refractive outcomes at 3 month postoperative period in paediatric patients undergoing cataract surgery with primary placement of an intraocular lens. Methodology : This randomized interventional study of 31 eyes (24 patients) that successfully underwent cataract surgery and intraocular lens implantations. All patients were 12 years old and below. Intraocular lens power calculations were made using either SRK II or Modified Formula For Paediatric IOL Calculation. The postoperative refractive outcome was taken as the spherical equivalent of the refraction at 3 month postoperative follow-up. The prediction error was taken as the absolute difference between the predicted and the actual refraction. The data were analysed to compare the mean prediction error between SRK II and Modified Formula and evaluate the predictability. Results : The mean prediction error in the SRK II group was 1.03 (0.69) D while in Modified Formula 1.14 (1.19) D. The SRK II group showed lower prediction error of 0.11 D compared to Modified Formula group, but this was not statistically significant XIV (p > 0.05). 18.75% eyes in SRK II group achieved good predictability i.e. the refraction postoperatively was within± 0.5 D from predicted refraction compared to 46.67% eyes in the Modified Formula group. However the difference of the predictability between the two fonnulas was also not statistically significant. Conclusion We would like to conclude that the predictability of postoperative refraction in paediatric cataract surgery is comparable between Modified Formula and SRK II fonnula. The existence of the Modified Fonnula provides an alternative to the ophthalmologist for intraocular lens calculation in paediatric patients.